2021
DOI: 10.1016/j.ymgmr.2021.100761
|View full text |Cite
|
Sign up to set email alerts
|

Adult GAMT deficiency: A literature review and report of two siblings

Abstract: Guanidinoacetate methyltransferase (GAMT) deficiency is a creatine deficiency disorder and an inborn error of metabolism presenting with progressive intellectual and neurological deterioration. As most cases are identified and treated in early childhood, adult phenotypes that can help in understanding the natural history of the disorder are rare. We describe two adult cases of GAMT deficiency from a consanguineous family in Pakistan that presented with a history of global developmental delay, cognitive impairm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…CCDS2 in an adult patient was first described in 2003, and an estimated 25 cases have been reported since then. Children with CCDS2 should receive timely treatment to reduce the risk of developing severe mental and intellectual disabilities in adulthood ( 5 , 15 , 16 , 27 ). In the present study, Patient 1 was diagnosed at the age of 4 years and had a normal developmental outcome after >10 years of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…CCDS2 in an adult patient was first described in 2003, and an estimated 25 cases have been reported since then. Children with CCDS2 should receive timely treatment to reduce the risk of developing severe mental and intellectual disabilities in adulthood ( 5 , 15 , 16 , 27 ). In the present study, Patient 1 was diagnosed at the age of 4 years and had a normal developmental outcome after >10 years of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several nations are screening different IEMs according to their prevalence in that population [83,84] as presented in Table 3 with three most prevalent groups of disorders. In our country (Pakistan), there is no newborn screening program yet available for the screening of inherited metabolic disorders, hence we are making efforts to establish NBS in our country, [9,42,45,62,[85][86][87][88][89] although scarce data are available on such disorders in Pakistan. [9,62,[85][86][87][88][90][91][92][93][94] On the other hand, reports from Pakistan show that burden of inherited disorders is quite high due to consanguinity, hence there is a dire need to develop a NBS program, which can help to minimize the burden of such disorders from the society especially focus on aminoacidopathies, organic acidemias, and fatty acid oxidation disorders.…”
Section: Efforts To Initiate Nbs Program In Asian and Other Countriesmentioning
confidence: 99%
“…Furthermore, it has been reported that amino acids are also involved in major depressive disorders that can be screened by amino acid profiling [34], so the current method can also help to screen such types of disorders. Thus, there is a need for an NBS program in developing countries like Pakistan because the main goal of the NBS program is to reduce the morbidity and mortality of different inborn metabolic disorders [35][36][37][38][39][40][41][42], so such sensitive and specific analytical methods will be helpful in these efforts. Efficient analytical methods like the one reported in the current study can be applied in the NBS program to identify affected children with diseases like BCAAs, PKU, Maple Syrup Urine Disease, Tyrosinemia type II, Citrullinemia type I and type II, etc.…”
Section: Applications Of This Assaymentioning
confidence: 99%